# Concrete Mathematics Book: Worked example for “Lines in the Plane” Induction Step

In the book Concrete Mathematics by Graham, Knuth, and Patashnik there is a section in Chapter 1 called “Lines in the Plane”. See the book for details but it is, basically , a question of what is the max number of $L_n$ areas defined by $n$ lines through the plane they are on. So a plane with no lines through it has 1 region, one line has 2 regions, three lines has 7 regions, etc.

# The Recurrence and Closed Form

The recurrence (labelled as 1.4 in the book) is

\[\begin{align} L_0 & = 1\\ L_n & = L_{n-1} + n \text{, for n > 0} \end{align}\]And the proposed closed form (labelled as 1.6 in the book) we want to prove via induction is

\[L_n = \frac{n(n+1)}{2} + 1 \text{, for n > 0}\]# The Book’s Presentation of the Induction Step

The book says:

The key induction step is:

\[L_n = L_{n-1} + n = (\frac 12(n-1)n+1) + n = \frac 12n(n+1)+1\]

I found this quite terse and not fully clear on first reading; I realised I needed more practice at induction. Once a bit more versed in this topic I realised it was nice example of induction. I shall attempt to explain my take on it here. Firstly the recurrence again:

\[\begin{align} L_0 & = 1\\ L_n & = L_{n-1} + n,\ \ for\ \ n > 0 \end{align}\]And then the proposed closed form again:

\[L_n = \frac{n(n+1)}{2} + 1\]What we want is to “link” the two together. So we can take the “framework” of the recurrence above and “plug in” the $L_{n-1}$ closed form. The $L_{n-1}$ closed form is, literally, subtracting one from the $L_n$ closed form terms:

\[L_{n-1} = \frac{(n-1)n}{2} + 1\]So, once more with gusto and blue highlighting to show the “plugging in”, the recurrence is

\[L_n = \color{blue}{L_{n-1}}\color{#3d4144} + n,\ \ for\ \ n > 0\]Now we plug in the $L_{n-1}$ version of the closed form

\[L_n = \color{blue}{\frac{(n-1)n}{2} + 1}\color{#3d4144} + n\]Then (with Algebra!) we can prove the induction

\[\begin{align} L_n & = \color{blue}{\frac{(n-1)n}{2} + 1}\color{#3d4144} + n \\ & = \frac{(n-1)n}{2} + \frac 22 + \frac{2n}{2} \\ & = \frac{n^2 - n + 2 + 2n}{2} \\ & = \frac{n^2 + n + 2}{2} \\ & = \frac{n(n + 1) + 2}{2} \\ & = \frac{n(n + 1)}{2} + \frac 22 \\ & = \frac{n(n + 1)}{2} + 1 \end{align}\]And so we get our closed form back meaning the induction is complete.